Mixed ionic-electronic YSZ/Ni composite for SOFC anodes with high electrical conductivity - Fonseca, F. C.; de Florio, D. Z.; Esposito, V; Traversa, E.; Muccillo, ENS; Muccillo, R. (Electrochemical Soc Inc, 2006)
The preparation of the ZrO(2):8 mol % Y(2)O(3)/NiO (YSZ/NiO) composites by a modified liquid mixture technique is reported. Nanometric NiO particles dispersed over the yttria-stabilized zirconia (YSZ) were prepared, resulting in dense sintered specimens with no solid solution formation between the oxides. Such a feature allowed for the electrical characterization of the composites in a wide range of relative volume fraction, temperature, and oxygen partial pressure. The main results indicate that the composites have high electrical conductivity, and the transport properties in these mixed ionic-electronic (MIEC) composites are strongly dependent on the relative volume fraction of the phases, microstructure, and temperature. These parameters should hence be taken into consideration for the optimized design of MIEC composites for electrochemical applications. In this context, the composite was reduced under H(2) for the preparation of high-conductivity YSZ/Ni cermets for use as solid oxide fuel cell anode material with relatively low metal content. (c) 2005 the Electrochemical Society. [DOI:10.1149/1.2149312] All rights reserved.